Production, crystallization and X‐ray diffraction analysis of a complex between a fragment of the TssM T6SS protein and a camelid nanobody. Issue 3 (1st March 2015) - Nguyen, Van Son; Spinelli, Silvia; Desmyter, Aline; Le, Thi Thu Hang; Kellenberger, Christine; Cascales, Eric; Cambillau, Christian; Roussel, Alain
<x xml:space="preserve">Abstract</x> The type VI secretion system (T6SS) is a machine evolved by Gram‐negative bacteria to deliver toxin effectors into target bacterial or eukaryotic cells. The T6SS is functionally and structurally similar to the contractile tail of the Myoviridae family of bacteriophages and can be viewed as a syringe anchored to the bacterial membrane by a transenvelope complex. The membrane complex is composed of three proteins: the TssM and TssL inner membrane components and the TssJ outer membrane lipoprotein. The TssM protein is central as it interacts with both TssL and TssJ, therefore linking the membranes. Using controlled trypsinolysis, a 32.4 kDa C‐terminal fragment of enteroaggregative Escherichia coli TssM (TssM32Ct) was purified. A nanobody obtained from llama immunization, nb25, exhibited subnanomolar affinity for TssM32Ct. Crystals of the TssM32Ct–nb25 complex were obtained and diffracted to 1.9 Å resolution. The crystals belonged to space group P64, with unit‐cell parameters a = b = 95.23, c = 172.95 Å. Molecular replacement with a model nanobody indicated the presence of a dimer of TssM32Ct–nb25 in the asymmetric unit.